PENERAPAN MODEL PROJECT BASED LEARNING BERBASIS LESSON STUDY UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM DAN SOSIAL KELAS V - Fatmawati; R.Teti Rostikawati; Tine Aryati (STKIP Subang, 2023)
This study aims to enhance scientific knowledge and improve science learning outcomes among students in class V-A at Lawanggintung State Elementary School 2, located in Bogor City, during the odd semester of the 2023/2024 academic year. The research methodology employed in this study is Collaborative Classroom Action Research, based on the lesson study approach and utilizing the project based learning model. The present study was conducted through the establishment of collaborative partnerships between researchers and other stakeholders, with the aim of identifying issues, devising implementation strategies, and engaging in reflective practises pertaining to the learning process. The participants of this study consisted of 21 students enrolled in class V-A at SDN Lawanggintung 2, located in Bogor City. The sample comprised 11 female students and 10 male students. The primary objective of this study is to enhance the academic achievements of students in the fifth grade, namely in the fields of Natural and Social Sciences. This study presents the findings from the assessment of the first and second cycles. The acquisition of study data was facilitated by researchers through the utilization of direct tests, the observation of learning outcomes, and the observation of learning implementation. The presented statistics indicate a notable improvement in student learning outcomes after the implementation of the project based learning model. The evidence for this assertion is substantiated by the notable attainment of comprehensive learning objectives by students in cycle I and II, demonstrating significant improvement. During the first cycle, the learning completeness of pupils was recorded at 67%. In the subsequent cycle, the learning completeness increased to 86%. This accomplishment demonstrates a growth of 19% between Cycle I and Cycle II. The findings of this study indicate that the research conducted in class V-A of SDN Lawanggintung 2 Bogor City yielded positive consequences, namely in terms of enhancing students' learning achievements in Natural and Social Sciences courses through the implementation of the project based learning model.